THE EFFECT OF ONLINE SHOPPING EXPERIENCE AND BRAND IMAGE ON LENOVO LAPTOP PRODUCT PURCHASE DECISIONS THROUGH VIRAL MARKETING AS AN INTERVENING VARIABLE - Anung Widodo; Agus Wahyudin; Samsul Rizal (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This research aims to analyze the influence of online shopping experience and brand image on purchasing decisions for Lenovo laptop products through viral marketing as an intervening variable. .The Jakarta APP Polytektnik case study is the subject of this research. The research was conducted on 180 respondents using quantitative descriptive methods. Sampling using non-probability sampling technique, namely purposive sampling.The survey method used in collecting data was using a questionnaire instrument. This research is explanatory research, which is a study that explains the position of the variables studied in a study by processing it using SmartPLS 4.0 software.. This research proves the influence of online shopping experience has a positive and significant influence on purchasing decisions, brand image has a positive and significant influence on purchasing decisions, online shopping experience has a positive and significant influence on viral marketing, brand image has a positive and significant influence on viral marketing, online shopping experience has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, and viral marketing has a positive and significant effect on purchasing decisions. Keywords: Online shopping experience, Brand Image, Viral marketing,Purchase decision